A new chronology for the end-Triassic mass extinction - Deenen, M; Ruhl, M; Bonis, N; Krijgsman, W; Kuerschner, WM; Reitsma, M; van Bergen, M (2010)
The transition from the Triassic to Jurassic Period, initiating the 'Age of the dinosaurs', approximately 200 Ma, is marked by a profound mass extinction with more than 50% genus loss in both marine and continental realms. This event closely coincides with a period of extensive volcanism in the Central Atlantic Magmatic Province (CAMP) associated with the initial break-up of Pangaea but a causal relationship is still debated. The Triassic-Jurassic (T-J) boundary is recently proposed in the marine record at the first occurrence datum of Jurassic ammonites, post-dating the extinction interval that concurs with two distinct perturbations in the carbon isotope record. The continental record shows a major palynological turnover together with a prominent change in tetrapod taxa, but a direct link to the marine events is still equivocal. Here we develop an accurate chronostratigraphic framework for the T-J boundary interval and establish detailed trans-Atlantic and marine-continental correlations by integrating astrochronology, paleomagnetism, basalt geochemistry and geobiology. We show that the oldest CAMP basalts are diachronous by 20 kyr across the Atlantic Ocean, and that these two volcanic pulses coincide with the end-Triassic extinction interval in the marine realm. Our results support the hypotheses of Phanerozoic mass extinctions resulting from emplacement of Large Igneous Provinces (LIPs) and provide crucial time constraints for numerical modelling of Triassic-Jurassic climate change and global carbon-cycle perturbations. © 2010 Elsevier B.V. All rights reserved.